Peran PMO dan Analisis Tingkat Kepatuhan Menelan Obat pada Pasien Tuberkulosis Paru di Puskesmas Palembang: Dampak terhadap Kesembuhan - Suarni, Ertati; Badri, Putri Rizki Amalia; Hidayah, Arini Alfa (Jurnal Ners, 2023)
Pulmonary tuberculosis (TB) is a chronic infection caused by Mycobacterium tuberculosis, which is one of the top 10 leading causes of death worldwide. Treating pulmonary TB using the DOTS strategy ensures the involvement of a Directly Observed Treatment (DOT) Supervisor, ensuring patient compliance and regular treatment for successful recovery. This study aims to analyze the role of the DOT Supervisor (PMO) in patient compliance and its impact on the recovery of pulmonary TB patients at Merdeka Community Health Center in Palembang. The research was designed as a cross-sectional observational quantitative study, with a sample size of 31 individuals who completed a 6-month treatment and provided complete data. The results of the study revealed that the PMO played a significant role and fulfilled their duties according to the DOTS strategy. The PMO’s role was categorized as supportive in 61.3% of cases and non-supportive in 38.7% of cases. The level of compliance in taking medication among pulmonary TB patients was 74.2%, while non-compliance accounted for 25.8%. There was a significant relationship between the PMO’s role and patient adherence to medication intake guidelines in pulmonary TB patients at Merdeka Community Health Center, with an R-value of 27.800. In conclusion, the research findings indicate a significant relationship between the PMO’s role, medication compliance, and its impact on recovery.